2022
DOI: 10.1186/s12888-022-03855-w
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatry’s role in the prevention of post-intensive care mental health impairment: stakeholder survey

Abstract: Background Many critical illness survivors experience new or worsening mental health impairments. Psychiatry consultation services can provide a critical role in identifying, addressing, and preventing mental health challenges during and after admission to the acute medical care setting. However, psychiatry involvement in the ICU setting is lower than in other hospital settings and the conventional process in many hospitals requires other care providers to request consultation by psychiatry. De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…“The psychiatrists continue to rely on telehealth for treating psychiatric and substance use disorders, and the regulatory changes made at the beginning of the Public Health Emergency to increase access to these services continue to be essential for doctors and patients alike”(American Psychiatric Association, 2021). Telehealth or telepsychiatry can improve access to healthcare, increase delivery options and improve patient outcomes (Bieber et al, 2022; MHCC, 2020; Torales et al, 2022). Patients and providers are generally satisfied with telepsychiatry services.…”
Section: Discussionmentioning
confidence: 99%
“…“The psychiatrists continue to rely on telehealth for treating psychiatric and substance use disorders, and the regulatory changes made at the beginning of the Public Health Emergency to increase access to these services continue to be essential for doctors and patients alike”(American Psychiatric Association, 2021). Telehealth or telepsychiatry can improve access to healthcare, increase delivery options and improve patient outcomes (Bieber et al, 2022; MHCC, 2020; Torales et al, 2022). Patients and providers are generally satisfied with telepsychiatry services.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the insufficient participation of psychiatry in the ICU underscores the necessity for enhanced psychological assistance. Nevertheless, differing interpretations of psychiatry's function and possible disagreements among healthcare professionals continue to impede a cooperative approach [ 61 ]. In order to effectively treat the physical, cognitive, and psychological concerns of individuals with PICS, it is crucial to have proactive interdisciplinary collaboration.…”
Section: Reviewmentioning
confidence: 99%
“…Previous studies reported a relationship between delirium and physical impairment [ 56 ]. On the other hand, mental disorders, such as anxiety, depression, and post-traumatic stress disorder, were not associated with delirium [ 57 ]; however, psychiatric consultation services are offered to ICU patients with the aim of attenuating the mental component of PICS through the management of delirium [ 58 ]. Delirium may be regarded as an important factor affecting the outcome of PICS centered on cognitive dysfunction and may be controlled with appropriate assessments and management.…”
Section: Prognosis Of Sadmentioning
confidence: 99%